ANALISIS OVERALL EQUIPMENT EFFECTIVENES (OEE) UNTUK MENENTUKAN EFEKTIFITAS MESIN SONNA WEB - Agustinus Eko Susetyo (Universitas Sarjanawiyata Tamansiswa, 2017)
Demand of composite as aeronatics material is incresing. Itâ€™s light weight, high specific strength, are become a favour of research. Fiber volume Fraction (FVF) is one of important factor on making of composite. The volume ratio between FVF and the resin is affecting its mechanical properties. In this reaserach there were three ratio varation between fiber and the resin. Bending and shear test were conducted through out this research. Results show that, the ductility increased due to the increased of its ratio, but itâ€™s shear stressare decresed.Â